Islamic Revivalism in the Arab World and Its Dialogue with the West: The Homo Culturus Perspective (American Journal of Islam and Society, 2014)
This paper seeks to underline two features of transformation in the Arab world since the late 1960s. First, that region’s religious transformation or ṣaḥwah(awakening) has been a general and overwhelming phenomenon. The pulse of Islam’s global surge can be easily observed at various levels of contemporary Arab countries: the individual and the collective, as well as their political behavior and organization. Second, the great tension between the West and Islam, particularly after 9/11, constituted a sort of change in the relationship between these two parties. I argue that these tensions could be reduced and minimized if the West were to improve its linguistic and cultural ties with Arab societies. The perspective of cultural sociology is very helpful in clarifying how to enhance such a dialogue. I shed light on these two topics through what I call a Homo Culturus perspective.